Victimization in childhood as a suicide risk factor in adults - Dedic, Gordana J; Djordjević, Barbara; Dedić, Srdjan J (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. There is a burgeoning literature on the association between childhood victimization and the risk of suicidal behavior in early adolescence, while there is significantly less research showing this association in adults. The aim of our study was to examine whether victimization in childhood increased the likelihood of suicide attempt in adults. Methods. The sample consisted of 90 patients, 71 females and 19 males, aged 37.92 ± 11.04 years on average, hospitalized in the Day Hospital of the Clinic of Psychiatry Military Medical Academy, Belgrade, Serbia. The Juvenile Victimization Questionnaire (JVQ), Defense Style Questionnaire (DSQ-40) and Beck Depression Inventory were used for 50 patients following suicide attempt and in 40 patients who were on psychotherapeutic treatment due to various life crises not resulting in suicide attempt. According to the indications, we excluded the patients with psychosis (F20-F29, F30-31 and F 32.3), substances abuse (F10-F19) and dementia (F00-F09), satisfying International Classification of Diseases-10 version (ICD-10) (the World Health Organization criteria). The examinees of both groups were matched by age, education and marital status. Comparison of the patient groups was done by the Students’ t-test for the parametric features and Mann-Whitney U test for non-parametric data. Results. The suicide attempters had moderate depression (19.76 ± 10.52) and used immature defense mechanisms (p
Keywords: crime victims; child; suicide, attempted; adults; psychotherapy